Iterative Solutions for Solving Variational Inequalities and Fixed-Point Problems. (24th February 2021) - Zhu, Li-Jun; Shahzad, Naseer; Asiri, Asim
Abstract : In this paper, we are interested in variational inequalities and fixed-point problems in Hilbert spaces. We present an iterative algorithm for finding a solution of the studied variational inequalities and fixed-point problems. We show the strong convergence of the suggested algorithm.